Suppressing Pitx2 inhibits proliferation and promotes differentiation of iHepSCs. (November 2016) - Chen, Fei; Yao, Hao; Wang, Minjun; Yu, Bing; Liu, Qinggui; Li, Jianxiu; He, Zhiying; Hu, Yi-Ping
Highlights: Pitx2 knockdown decreased the expression of hepatic stem cell markers in iHepSCs. Pitx2 knockdown significantly inhibited the proliferation of iHepSCs. Proliferation inhibition was caused by G1/S transition arrest through p53-p21 pathway. Pitx2 knockdown promoted iHepSCs differentiation rapidly and efficiently. Abstract: Induced hepatic stem cells (iHepSCs) have great potential as donors for liver cell therapy due to their abilities for self-renewal and bi-potential differentiation. However, the molecular mechanism regulating proliferation and differentiation of iHepSCs is poorly understood. In this study, we provide evidence that the homeodomain transcription factor, Pitx2, is essential to maintain iHepSCs stem cell characteristics. Suppressing Pitx2 expression in iHepSCs by lentivirus mediated specific shRNA markedly reduced the expression of the hepatic stem cell-associated genes (Lgr5, EpCAM, and Sox9) with concomitant inhibition of proliferation by blocking the G1/S phase transition, and these phenotypic changes were reversed upon re-expression of Pitx2. Pitx2 knockdown also resulted in up-regulation of the p53-induced Cdk inhibitor p21, and down-regulation of its downstream effector CDK2-Cyclin E kinase complex. Furthermore, we observed that iHepSCs were more efficiently induced to differentiate into both hepatocytes and cholangiocytes when Pitx2 expression was suppressed, as compared to unmanipulated iHepSCs. These findings reveal that Pitx2 expression may be leveraged to control the status of iHepSCs during expansion in vitro to provide a strategy for further application of iHepSCs in liver cell therapy.